2020
DOI: 10.1002/jez.b.22943
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes of histone acetylation and methylation in bovine oocytes, zygotes, and preimplantation embryos

Abstract: Histone modifications play important roles in regulating chromatin dynamic changes. In this study, acetylated histone H3 lysine 9 and 18 (H3K9ac and H3K18ac), acetylated histone H4 lysine 5 and 8 (H4K5ac and H4K8ac), tri‐methylation histone H3 lysine 4 (H3K4me3), di‐methylation histone H3 lysine 9 (H3K9me2) are investigated in bovine oocytes, zygote, and preimplantation. During meiosis, H3K9ac and H3K18ac are erased after germinal vesicle breakdown, H4K8ac is erased after metaphase I (MI). Although H4K5ac is e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…Together with H3K27me3, H3K4me3 regulates the expression of genes related to embryonic development [40]. Wu et al found that the expression level of H3K4me3 was lower in embryos before the 8-cell stage in cattle embryos and that from the 16-cell stage to the blastocyst stage, the expression level of H3K4me3 increased significantly [41]. In this study, we performed immunofluorescence staining of H3K4me3 on mouse embryos at various developmental stages and found a similar pattern.…”
Section: Discussionsupporting
confidence: 68%
“…Together with H3K27me3, H3K4me3 regulates the expression of genes related to embryonic development [40]. Wu et al found that the expression level of H3K4me3 was lower in embryos before the 8-cell stage in cattle embryos and that from the 16-cell stage to the blastocyst stage, the expression level of H3K4me3 increased significantly [41]. In this study, we performed immunofluorescence staining of H3K4me3 on mouse embryos at various developmental stages and found a similar pattern.…”
Section: Discussionsupporting
confidence: 68%
“…Integrated with these individual gamete responsibilities, the situation is further complicated during syngamy, as it is now well described that the oocyte under certain circumstances has the capacity to repair the male DNA contribution [26], so that lack of normal oocyte maturation could potentially also compromise the oocyte's DNA repair mechanisms. With respect to the oocyte's haploid duties, histone H3/H4 acetylation pathways are key to achieving a nucleus ready for syngamy [27] and disequilibrium in the oolema has also been shown to prevent gamete fusion [5].…”
Section: Discussionmentioning
confidence: 99%
“…Conceptually, the male and female pronuclei have two roles or duties which can be negatively impacted by the presence of a damaged DNA molecule; these duties can be divided into tasks that occur before syngamy which can be referred to as their “haploid duty” and those that carry on after syngamy referred to as their “diploid duty.” Integrated with these individual gamete responsibilities, the situation is further complicated during syngamy, as it is now well described that the oocyte under certain circumstances has the capacity to repair the male DNA contribution [ 26 ], so that lack of normal oocyte maturation could potentially also compromise the oocyte’s DNA repair mechanisms. With respect to the oocyte’s haploid duties, histone H3/H4 acetylation pathways are key to achieving a nucleus ready for syngamy [ 27 ] and disequilibrium in the oolema has also been shown to prevent gamete fusion [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…During oocyte development, there are various histone modifications, including acetylation and methylation, which can regulate nuclear-cytoplasmic balance, gene expression, and developmental potential [58][59][60]. Histone methylation refers to the transfer of methyl groups to lysine and arginine residues on the extended histone tails of nucleosomes.…”
Section: Histone Modificationsmentioning
confidence: 99%
“…Another modification, histone H3 lysine K27 trimethylated (H3K27me3), is a suppressive modification of gene transcription which, together with histone H3 lysine K9 trimethylated (H3K9me3), occupies gene bodies to form bivalent regions in bovine oocytes [59]. These modifications decrease before embryonic genome activation and then increase with cell division [60].…”
Section: Histone Modificationsmentioning
confidence: 99%